Corticosteroid-free Kidney Transplantation Improves Growth. Issue 6 (June 2015) - Webb, Nicholas J. A.; Douglas, Sarah E.; Rajai, Azita; Roberts, Stephen A.; Grenda, Ryszard; Marks, Stephen D.; Watson, Alan R.; Fitzpatrick, Maggie; Vondrak, Karel; Maxwell, Heather; Jaray, Jeno; Van Damme-Lombaerts, Rita; et al.
<x xml:space="preserve">Abstract</x> Background Corticosteroid withdrawal (CW) after pediatric kidney transplantation potentially improves growth while avoiding metabolic and other adverse events. We have recently reported the results of a 196 subject randomized controlled trial comparing early CW (tacrolimus, mycophenolate mofetil (MMF), daclizumab, and corticosteroids until day 4) with tacrolimus, MMF, and corticosteroid continuation (CC). At 6 months, CW subjects showed better growth with no adverse impact on acute rejection or graft survival (Am J Transplant 2010; 10: 828–836). This 2-year investigator-driven follow-up study aimed to determine whether improved growth persisted in the longer term. Methods Data regarding growth, graft outcomes and adverse events were collected at 1 year (113 patients) and 2 years (106 patients) after transplantation. The primary endpoint, longitudinal growth calculated as delta height standard deviation score, was analyzed using a mixed model repeated measures model. Results Corticosteroid withdrawal subjects grew better at 1 year (difference in adjusted mean change, 0.25; 95% confidence interval, 0.10, 0.40; P = 0.001). At 2 years, growth remained numerically better in CW subjects (0.20 (−0.01, 0.41); P = 0.06), and significantly better in prepubertal subjects (0.50 (0.16, 0.84); P = 0.004). Bacterial and viral infection was significantly more common in CW subjects at 1 year only. Corticosteroid withdrawal and CC subjects received similar exposure to both tacrolimus and MMF at 1 and 2 years. No significant difference in patient or graft survival, rejection, estimated glomerular filtration rate, or other adverse events was detected. Conclusion Early CW effectively and safely improves growth up to 2 years after transplantation, particularly in prepubertal children.